Superior vena cava syndrome due to mediastinal Gardner fibroma presenting as syncope. Issue 12 (4th December 2019) - Manappallil, Robin George; Nambiar, Harilal; Mampilly, Neena; Harigovind, Della
Abstract : Superior vena cava (SVC) syndrome refers to the clinical manifestation due to an obstruction in the SVC; resulting in decreased venous return from the head, neck and upper extremities. The obstruction can occur either due to tumour invasion of the vessel wall with associated thrombus or due to vessel wall compression by the tumour mass. The patient being reported is a young male who presented with recurrent episodes of syncope and was found to have mediastinal Gardner fibroma causing SVC syndrome. Gardner fibroma is a benign soft tissue lesion; and its occurrence in the mediastinum resulting in SVC syndrome has not been reported yet.